SEASONAL VARIATION (IN 2014) OF WAVE ATTENUATION ENERGY IN MANGROVE AREA IN BENOA BAY , BALI - Setyo Kuntoro, Wahyu
The effect of the mangrove vegetation presence towards seasonal wave attenuation energy variation in Benoa Bay, Bali, in 2014 has been simulated using SWAN (Simulating Wave Nearshore) model with multi-scale nested grid method, and unstructured grid used at domain 5 (D5) with the largest mesh 45.45 m2 and the smallest 0.01 m2. The model was forced using Cross Calibrated Multi Purposed (CCMP)wind data with resolution 14?o, and 1200?o bathymetry data derived from General Bathymetry Chart of the Oceans (GEBCO 30’) also Batimetri Nasional (BATNAS) with resolution 1/600° provided by Indonesia Geospatial Agency (BIG). Obtained data from three observed point in the model shows that the presence of mangrove vegetation was decreasing the wave height. The percentage of wave attenuation and the change of wave height during propagation during east monsoon (JJA) are higher than the other seasons. Furthermore, wave direction changes drastically on transition months (February, March, April). The wave energy is decreasing significantly and peak period shifts to smaller period because of the mangrove vegetation presence.